2010
DOI: 10.1017/s002211200999293x
|View full text |Cite
|
Sign up to set email alerts
|

On the turbulent Prandtl number in homogeneous stably stratified turbulence

Abstract: In this paper, we derive a general relationship for the turbulent Prandtl number Pr t for homogeneous stably stratified turbulence from the turbulent kinetic energy and scalar variance equations. A formulation for the turbulent Prandtl number, Pr t , is developed in terms of a mixing length scale L M and an overturning length scale L E , the ratio of the mechanical (turbulent kinetic energy) decay time scale T L to scalar decay time scale T ρ and the gradient Richardson number Ri . We show that our formulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 26 publications
5
76
0
1
Order By: Relevance
“…4 of Venayagamoorthy and Stretch (2010), are consistent with these conditions. This is not surprising: any monotonically increasing function linking the neutral stability limit: Pr T | Ri=0 = Pr 0 ≈ 0.7−0.8 with the large Ri limit: Pr T = R −1 ∞ Ri (e.g., the simple interpolation: Pr T = Pr 0 + R −1 ∞ Ri) would also look reasonable.…”
Section: Energy-budget Argumentssupporting
confidence: 77%
“…4 of Venayagamoorthy and Stretch (2010), are consistent with these conditions. This is not surprising: any monotonically increasing function linking the neutral stability limit: Pr T | Ri=0 = Pr 0 ≈ 0.7−0.8 with the large Ri limit: Pr T = R −1 ∞ Ri (e.g., the simple interpolation: Pr T = Pr 0 + R −1 ∞ Ri) would also look reasonable.…”
Section: Energy-budget Argumentssupporting
confidence: 77%
“…The maximum value of the flux Richardson number: R ∞ ≈ 0.2 has been determined from various experimental, large-eddy simulation (LES) and direct numerical simulation (DNS) data for extremely strong static stabilities, namely, for the values of Ri between 1 and 10 2 , at which Ri f definitely levels off (e.g., Yamada 1975;Stroscio 1982;Zilitinkevich et al , 2008Zilitinkevich et al , 2009Stretch et al 2009;Venayagamoorthy and Stretch 2010). It is remarkable that the coefficient 1/R ∞ ≈ 5 in Eq.…”
Section: Alternative Derivationmentioning
confidence: 99%
“…Venayagamoorthy & Stretch [9] found that Γ ∞ = 1/3 fits the data corresponding to Ri f ∞ = 0.25 [7]. Pr t0 is taken to be 0.7 from the previous discussion.…”
Section: The Turbulent Prandtl Numbermentioning
confidence: 94%
“…Additionally, the analytical Pr t model of Venayagamoorthy & Stretch [9] (hereafter VS10) is considered. The authors provided a theoretical modification to the empirical formulation of Schumann & Gerz [8] based on DNS data [5,7].…”
Section: The Turbulent Prandtl Numbermentioning
confidence: 99%
See 1 more Smart Citation